FACTS : modelling and simulation in power networks - Acha, Enrique (Wiley, 2004)
The first book to provide comprehensive coverage of FACTS power systems modeling and simulation.* Detailed coverage of the development of FACTS controllers and guidance on the selection of appropriate equipment* Computer modelling examples of the FACTS controllers for steady-state and transient stability systems* Numerous case studies and practical examples.